VOLUME 4, NO 1 (2016) - Chief, Editor In (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Dear readers, you are holding the sixth issue (Vol IV, No 1) of Aro-The Scientific Journal of Koya University in your hand. With this issue Aro is starting a new era as the first ever internationally listed Scientific Journal in Kurdistan Region/Iraq history. Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this index is under consideration by Thomson Reuters to be accepted in the Science Citation Index Expanded™ (SCIE). This is a great achievement that we share with our academic communities. Aro is starting its fourth year journey in leading the quality of regional scientific publications with global impact. The editorial team is determined to keep the path of such a mission and sustain the future publications of Aro with quality and reliability in mind.Despite the continuous financial crises which has had a great impact on scientific research and particularly universities in our region, Aro is lasting to receive good numbers of well-motivated quality papers that shows its steadily growing trust among researchers in the region. With increasing demands by volume of submission, The Associate Editorial of Aro has grown larger, well dedicated and our meetings are richer. Our colleagues with great passion are contributing to the long-term visions of Aro.Aro was created with long-term visions to become accessible to all researchers in Kurdistan and beyond, covering a wide range of scholarly disciplines in sciences. The focus of the journal is to reflect that of Koya University, namely promoting scientific knowledge and research in Kurdistan and secure a brighter future in education with global representation. Aro aspires to become a channel for exchanging scholarly research by establishing academic connections between scholars globally.Aro is a journal of original scientific research, global news, review paper, letters and commentary. The Aro Scientific Journal is a peer-reviewed, open access journal that publishes original research articles as well as review articles in areas of natural sciences and technology. In this issue you will have access to genuine research paper in variety of areas such as; Petroleum, Physics, Chemical Engineering, biochemistry, engineering and material.The warm response from researchers, academics and professionals in the last four years has made us to create a wider Editorial Board which serves the wider submitted scientific manuscripts. However, it is clear that to have a dedicated and well organized editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work for publication in Vol IV, No 1 of the journal, as well as, our thanks are extended to the 16 peer-reviewers from the Universities worldwide for their efforts in reviewing and enabling this issue of Aro. Your support and feedback are invited and appreciated. Dilan M. RostamEditor-in-ChiefWali M HamadExecutive Publisher Dilan M. Rostam, Shwan K. Rachid, Salah I. Yahya, Sarkawt S. AbdulrahmanExecutive Editorial Board